2009
DOI: 10.1016/j.nbt.2009.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Natural antibodies and cancer

Abstract: The innate or natural immunity is the basis and key for all immune processes. Specific receptors on macrophages, dendrites, NK cells and natural antibodies producing B cells act as a first line defense and remove all 'foreign' and potentially harmful substances, that is, bacteria, viruses, cellular waste, modified molecules and, most importantly, cancer cells. Recognition and removal of transformed cells is a lifelong task of immune surveillance processes. Antibodies are hallmark components of this anti-cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
101
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(105 citation statements)
references
References 62 publications
4
101
0
Order By: Relevance
“…The data obtained demonstrated that the loss of C3 activation, whose fragments were found to specifically accumulate in vessels and stroma in and around the incipient cancers, was responsible for the dramatic increase in the aggressiveness of neu C mammary tumors. Concomitantly, as had already been demonstrated in cancer patients, 32,33,34 spontaneous antitumor antibodies increased in neuT mice during the course of tumor progression. 24 Taken together, these observations suggest that the complement system can take on a tumor-inhibiting role that is played out through the activation of the classical pathway.…”
Section: Discussionsupporting
confidence: 71%
“…The data obtained demonstrated that the loss of C3 activation, whose fragments were found to specifically accumulate in vessels and stroma in and around the incipient cancers, was responsible for the dramatic increase in the aggressiveness of neu C mammary tumors. Concomitantly, as had already been demonstrated in cancer patients, 32,33,34 spontaneous antitumor antibodies increased in neuT mice during the course of tumor progression. 24 Taken together, these observations suggest that the complement system can take on a tumor-inhibiting role that is played out through the activation of the classical pathway.…”
Section: Discussionsupporting
confidence: 71%
“…Glycosylation may also modulate protein processing and hence affect exposure of new epitopes as shown in Rasmussen's encephalitis, where an N-glycan blocks proteolysis of a neuronal glutamate receptor and the establishment of a short peptide epitope [40]. Several human monoclonal antibodies have been shown to be directed to epitopes affected by glycosylation [41][42][43][44][45] but it is currently unclear if these antibodies define glycopeptide epitopes per se. The O-glycopeptide autoantibody epitopes identified on human MUC1 and murine podoplanin are therefore important models for this type of epitope.…”
Section: Discussionmentioning
confidence: 99%
“…This is beyond the scope of this review but we note this literature. It would certainly be literature that Dr. Ron Asherson would have enjoyed reading [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37].…”
Section: Resultsmentioning
confidence: 99%